Operations and R & D in a association small that operates with projects - Brito, Max Leandro de Araújo; Melo, Tamara Patrícia Filgueira de; Cunha, Sheila de Lima; Sousa Neto, Manoel Veras de (Pubvet, 2015)
Organizational functions are indispensable for the maintenance of activities ofany institution, regardless of size, much less type or characteristics. Two important functions that are closely related to the development of products and services are operating, and research and development (R & D). Taking into account the context presented, the research aims to characterize the performance of the functions of operations, research and development in a small membership organization. The methodology is to review the literature that discusses the functions of operations, research and development, project management, third sector and social economy, and implementation of a roadmap for semi-structured to perform an in-depth interview, in the case is an exploratory research descriptive type diagnostic, predominantly qualitative. Among the results are the perception that the organization has an operations function with difficulties in moving out of rural areas in addition to lack of use of computers and the Internet. Thus, the research points to the difficulty of moving goods by not having control over the means of urban transport, and use old technology for the development of activities. One of the limitations of the research is the difficulty of meeting the specific activities of each organizational function due to the small size of the organization.
Keywords: Production; Information Technology; Associations